Troens grund - Sørensen, Henning (Grundtvig-Studier, 1977)
The Basis of Faith by Henning Sørensen In the period 1811-23 Grundtvig is forced into a continuous process of differentiation in the Bible in an attempt to find the Word of God that is the basis of faith. But in the course of the Church year 1822-23 this process is interrupted by Grundtvig’s discovery of the power of the audible word, a discovery that the audible word is better suited to being the word by which faith is born, fed, strengthened, and therefore, grows. The word of man is not just a sound, but can be “tuned” to have a spiritual content. In other words, faith is born and strengthened by the word being heard, and faith in this audible word implies that it seeks to be professed. The unparalleled discovery in 1825 is therefore already being prepared for in 1823, even though right up to the 9th Sunday in Trinity 1825 Grundtvig may be retaining the written word as the basis of faith, in an attempt to defend himself against unbelievers. In 1832 Grundtvig reaches a new understanding of mankind that goes against his Lutheran origins. Recreation must now start from what is created by the Creation and what has fallen of Man at the Fall. This Man is capable of believing and verbalising this faith. The life of Jesus was a divine life lived under the laws of human nature. This life can be linked to Man’s by Man being baptized with Jesus’ baptism and thereby sharing in the blessing that was heard at His baptism. With regard to this starting-point, that is, baptism, Jesus is born and grows as a child together with Mankind to consummation. Since Man was created by a Creative Word, he should remain true to the purpose of creation through faith. But Man doubted, the Fall occurred, and faith became blind. It shrank until it was no more than a vague memory of the original life in God’s image. Through re-creation the heart hears a Word that corresponds to the original Word of Creation, and the faith created at the Creation is re-created into a Christian faith through the Word of faith that illuminates the truth. This does not mean, however, that the faith given to all people at the Creation has no further purpose. For that is precisely the faith which is the source of the Christian faith, and this faith will still be a prerequisite if men are to believe one another and human life is to be lived at all. The blind and the seeing faith, like the fallen and the raised man, are therefore of the same nature. But the seeing faith knows where truth is to be found and will be able to believe this truth if it can be helped towards it.